2020
DOI: 10.3389/fphar.2020.00225
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Midazolam Oral Solution for Sedative Hypnosis and Anti-anxiety in Children: A Systematic Review and Meta-Analysis

Abstract: Background: Midazolam is recommended by health guidelines for sedation and hypnosis in children. Oral solution is a suitable dosage form for children. But there is no conclusive evidence for sedative-hypnosis and antianxiety effects by midazolam oral solution in children.Methods: Relevant studies were identified through searching PubMed, Embase, Cochrane Library, CINAHL, International Pharmaceuticals, four Chinese electronic databases, and relevant lists. Two reviewers independently selected trials, assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 67 publications
1
20
0
1
Order By: Relevance
“…Cheng et al 14 realizou uma revisão sistemática com casos seriados de sedação em pacientes pediátricos com midazolam em solução oral. Nesta, revelou-se 106 casos alterações mentais incluindo 74 casos de choro, 9 casos de agitação, 6 casos de mordida labial, 6 casos de letargia, 5 casos de alucinações, 4 casos de excitação anormal, 1 caso de gritos e desorientação.…”
Section: Resultsunclassified
“…Cheng et al 14 realizou uma revisão sistemática com casos seriados de sedação em pacientes pediátricos com midazolam em solução oral. Nesta, revelou-se 106 casos alterações mentais incluindo 74 casos de choro, 9 casos de agitação, 6 casos de mordida labial, 6 casos de letargia, 5 casos de alucinações, 4 casos de excitação anormal, 1 caso de gritos e desorientação.…”
Section: Resultsunclassified
“…Pediatric patients are prone to fear and anxiety before surgery, which can lead to prolonged anesthesia induction time, longer stay in the PACU, increased consumption of analgesics, more complications, and prolonged wound healing time [ 18 ]. Oral administration of 0.5 mg/kg midazolam has good anxiolytic and amnestic effects, with a short duration of action, high acceptance by pediatric patients, and helps with the separation of the child from their parents [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, experts agree on the following recommendations: fasting solid food 6 h before surgery, fasting breast milk 4 h before surgery, refraining from clear fluids 2 h before surgery, and consuming liquid rich in carbohydrates (surgical energy) within 2 h before surgery is beneficial for the patient’s postoperative recovery [ 18 ]. Studies have shown that drinking a carbohydrate drink 2 h before surgery does not cause delayed gastric emptying and reduces postoperative insulin resistance, which can improve patient satisfaction and clinical outcomes [ 19 23 ]. Preoperative consumption of Outfast 5 ml/kg (Yichang Humanwell Pharmaceutical Co., ltd. China) within 2 h before surgery in this study, can relieve preoperative hunger, thirst, and anxiety, without increasing the risk of reflux or aspiration during surgery, thus, accelerating patient recovery, and shortening hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Drug efficacy can be achieved within 20 minutes, with a half-life of approximately 2.2 to 6.8 hours, significantly the drug effect does not seem to continue until 24 hours after surgery. [ 30 ] A study found that oral administration of 0.5 and 0.75 mg/kg MID provides equally good sedative and anti-anxiety effects in children. [ 31 ] Considering that the effectiveness and safety of MID are related to drug dosage, oral administration of 0.5 mg/kg MID solution is often chosen.…”
Section: Management Methods and Commonly Used Drugs For Pediatric Den...mentioning
confidence: 99%